Prilaku Non Voting dalam Pemilihan Kepala Daerah Lampung Timur Tahun 2015 (Studi di Kecamatan Way Jepara Kabuaten Lampung Timur) - Suwondo, Suwondo; Purba, Darmawan (Jurnal Analisis Sosial Politik, 2017)
On December 9, 2015 Lampung province has carried out the Local Leaders Election simultaneously in 8 Regency / City, but the number of abstainers were still high. East Lampung Leaders Election is one of elections with the highest number of abstainers, as many as 289.351 voters or 36.42% were abstained. This number is even greater than the votes of candidates elected which was 263.926 or 33.22%. This fact is interesting to be seen in the context of non-voting behaviors that affect voters that they do not vote in the election. Conceptually non-voting behavior can be mapped into 4 groups: (1) political technical factors; (2) technical factors; (3) political factors; and (4) ideological factors. This research was conducted in Way Jepara District by interviewing 100 respondents that were chosen through multi-stage random sampling. In addition, the data of the research is also supported by the results of interviews conducted to members of the Election Commission of East Lampung. The research found that 51% of respondents enrolled in the Electoral Register were; 44% had moved before the election, 4% died and 3% seriously ill / lost consciousness. Only 49% of respondents could be encountered in this study and the results showed 12% of respondents did not choose because of political factors, 8.16% due to political technical factors and 4.08% because of ideological factors. Generally, as many 37 respondents or 75% did not vote due to technical factors, for example, one does not choose because of the conditions and situations that hamper the voters to come to the polling stations. Some of the major indicators are; (1) family requisite, (2) health, (3) do not remember or forget, and (4) working consideration.In line with the evaluation results by the Election Commission of East Lampung, steps that need to be done to improve voters participation rates in order to reduce abstained are namely: (1) improving the population administration, (2) building an actual system of administration. (3) spreading more widely and evenly voters education, (4) disseminating the election process long before the election day and strengthening institutionally the organizers of local leaders election. Pada 9 Desember 2015 di Provinsi Lampung terlaksana pemilihan kepala daerah serentak 8 Kabupaten/ Kota, namun angka golput masih tinggi. Pilkada Lampung Timur merupakan salah satu pilkada dengan angka golput tertinggi sebanyak 289.351 pemilih atau 36,42% golput, angka golput ini bahkan lebih besar dibandingkan perolehan suara calon bupati terpilih sebesar 263.926 atau 33,22%. Fakta tersebut menarik untuk dilihat dalam kontek prilaku non voting yang mempengaruhi pemilih sehingga tidak menggunakan suaranya saat pilkada. Secara konseptual prilaku non voting dapat dipetakan dalam 4 kelompok yaitu: (1) faktor teknis politis; (2) faktor teknis; (3) faktor politis; dan (4) faktor ideologis. Penelitin ini di dilaksanakan di Kecamatan Way Jepara, dengan mewawancarai sebanyak 100 responden yang dipilih secara multy stage random sampling. Selain itu data penelitian didukung hasil wawancara dengan anggota KPUD Lampung Timur.Hasil penelitian menemukan bahwa, sebanyak 51% responden yang terdaftar di DPT ternyata 44% sudah pindah sebelum pemilihan, 4% meninggal dunia dan 3% sakit keras/hilang kesadaran. Hanya 49% responden yang dapat ditemui dalam penelitian ini dan hasilnya menunjukkan 12% responden tidak memilih karena faktor politis, 8,16% karena faktor teknis politis dan 4,08% karena faktor ideologis. Umumnya sebanyak 37 responden atau 75% tidak ikut memilih dikarenakan faktor teknis, yaitu seseorang tidak memilih karena kondisi dan situasi yang menghambat pemilih untuk datang ke tempat pemungutan suara. Beberapa indikator utamanya; (1) Keperluan keluarga, (2) Kesehatan, (3) Tidak ingat atau lupa, dan (4) Pertimbangan pekerjaan.Sejalan dengan hasil evaluasi KPUD Lampung Timur langkah yang perlu dilakukan untuk meningkatkan angka partisipasi pemilih sehingga dapat mengurangi golput antara lain: (1) penyempurnaan administrasi kependudukan, dan (2) membangun sistem administrasi kependudukan yang aktual. (3) pendidikan pemilih semakin secara luas dan merata, (4) sosialisasi proses pilkada jauh-jauh hari dan penguatan kelembagaan penyelenggara pemilihan kepala daerah.